A randomized, controlled, and clinical trial to evaluate the efficacy of electrical vestibular stimulation, compared to a sham control for the management of sleep and autonomic parameters in patients with Parkinson’s disease - Sai Sailesh kumar Goothy; Sudhir Gawarikar; Anita Choudhary; Potey Gajanan Govind; Manju Purohit; Ashish Pathak; Rohit Singh Chouhan; Mahadik Vijay Khanderao (Asian Journal of Medical Sciences, 2022)
Background: Electrical vestibular nerve stimulation (VeNs) was simple, non-invasive, and can administer the stimulus in a controlled manner. The studies related to the application of electrical VeNs in the management of sleep and autonomic parameters were sparse in the Indian population.